Effectiveness of the Implementation of the Complete Systematic Land Registration Program (PTSL) - Sugiyono, Sugiyono; Sri Darmadi, Nanang (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2026)
This study aims to analyze: 1)The process of implementing the complete systematic land registration program (PTSL) in Genuk District, Semarang City. 2) The effectiveness of the implementation of the complete systematic land registration program (PTSL) in Genuk District, Semarang City. This type of research is empirical legal research. The approach method in this research is a sociological juridical approach. The types of data in this research are primary and secondary data. The data collection method uses field techniques and library techniques. The analysis in this research is descriptive. The results of the study concluded: 1) The process of implementing the complete systematic land registration program (PTSL) in Genuk District, Semarang City is an effort by the government to realize legal certainty of land rights through comprehensive and systematic land registration. Its implementation involves the Semarang City Land Office, local government, and the community in the stages of socialization, data collection, verification, and certificate issuance. Based on Gustav Radbruch's theory of legal certainty, PTSL in Genuk District has fulfilled the principles of clear positive law, based on social facts, and is implemented consistently. Although there are administrative, technical, and social obstacles, through inter-agency coordination, the application of digital technology, and increasing public legal awareness, these obstacles can be overcome. With the achievement of more than 94 percent of land plots certified by 2025, PTSL in Genuk is considered successful in creating orderly land administration and strengthening legal certainty for the community. 2) The effectiveness of the implementation of the complete systematic land registration program (PTSL) in Genuk District, Semarang City, namely showing significant success in realizing legal certainty, orderly land administration, and improving community welfare through the issuance of land title certificates in a comprehensive, fast, and transparent manner. Based on an analysis of five factors of legal effectiveness, all elements of legal implementation, starting from clear legal substance, professional implementing officials, adequate means and facilities, to community participation and legal culture, have functioned optimally. PTSL in Genuk District is not only effective administratively with the achievement of more than 94 percent of land plots certified, but also effective substantively because it is able to raise public legal awareness, reduce land disputes, and open economic access through the legalization of land assets.